STATIC BENDING STRENGTH AND STIFFNESS IN JUVENILE AND ADULT WOOD OF FAST-GROWING Pinus taeda L. - Rosa, Talitha Oliveira; Iwakiri, Setsuo; Trianoski, Rosilani; Terezo, Rodrigo Figueiredo; Coelho, Leonardo Kellet; Righez, Joao Laryan Borges (Floresta, 2023)
Due to the high growth rates of the forests planted in Brazil and the variations of the mechanical properties within a tree, this study aimed to evaluate the strength (MOR) and stiffness (MOE) in static bending according to the juvenile and adult wood, and the grown-rings inclination at the transversal area of clean specimens of Pinus taeda. Subsequently, the woods were classified in its structural gradings. Pinus taeda logs with 30 years old had the growth rings delimited at every six years on the transversal area. The juvenile wood was represented by the zone of 0 to 6 years of growth (marked with red), and 6.1-12 years (blue). The zone of 12.1-18 (orange) was considered as transition wood and from 18.1-24 (green) and 24.1-30 years (yellow), adult wood. After the sawing, 25 boards were selected to the sawing of the specimens (n = 104) for the static bending test. Growth-ring inclination was measured as a function of the direction of the load applied at the bending test. Statistical tests were performed in a factorial scheme with the MOR and MOE to static bending. Factors were independent (mechanical properties and growth-rings inclination). The 0-6-year-old wood was not indicated for structural use. Woods between 12-30 years old showed a minimum compatible result to be classified for structural use. The inclination did not influence at the modulus of elasticity and strength at bending.